Some Topological Properties of CbX - Juan Carlos Ferrando (Journal of Function Spaces)
If X is a completely regular space, first we characterize those spaces CbX whose compact sets are metrizable. Then we use this result to provide a general condition for X to ensure the metrizability of compact sets in CbX. Finally, we characterize those spaces CbX that have a G-basis.